Efek penggunaan tepung umbi dan kulit bawang putih (Allium sativum Linn) sebagai feed additive terhadap penampilan produksi ayam petelur - Deko, Maria Karolina; Djunaidi, Irfan H.; Natsir, M. Halim (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
This study aims to evaluate the effect of giving Garlic and Allium sativum (TUKBP) Flour as feed additives on various levels of feeding in feed consumption, Hen Day Production (HDP), egg mass, feed conversion and Income Over Feed Cost (IOFC) in laying hens. A total of 320 laying hens strain Isa Brown produced by PT. Charoen Pokphand aged 30 weeks, divided into 8 treatments and 4 replications each replication using 10 chickens. The experimental design used was a Completely Randomized Design (CRD). Eight treatment groups were as follows: basal feed + 0% TUKBP as negative control feed (P0), basal feed + virginiamycin antibiotic 0.015% as positive control (P1), and basal feed + TUKBP 0.25% (P2), 0, 50% (P3), 0.75% (P4), 1.00% (P5), 1.25% (P6) and 1.50% (P7). Data were analyzed using ANOVA test, if there were significant differences between treatments continued with Duncan's Multiple Range test. The results showed that feed with the addition of TUKBP can improve the appearance of laying hens, although it has not matched the feed with the addition of antibiotics. The use of TUKBP to the level of 1.50% in feed does not cause negative effects for laying hens. Administration of TUKBP at 1.00% level (P5) is able to replace synthetic antibiotics or as organic additive feeds in laying chicken feed.